Moderation Social Influence on Influence Effort Expectancy Against Adoption of Innovation - Uke Prajogo; Lidia Andiani; Shafira Yana Yasmin (International Journal of Economics Accounting and Management, 2026)
This study aims to analyze the effect of effort expectancy on innovation adoption,moderated by social influence.The sample criteria determined by the researcher were:1. MSMEs that are members of ABM Preneur 2. Know or have used QRIS This study used a saturated sampling technique, resulting in a sample size of 90 individuals in the entire population.Data analysis and hypothesis testing were conducted using Smart PLS version 4.1.0.9.The results showed that H1 was accepted while H2 was rejected. Therefore, effort expectancy has a positive and significant effect on innovation adoption. Social influence does not moderate the effect of effort expectancy on innovation adoption.The limitation of this study is that it only analyzes the moderation of social influence on the effect of effort expectations on the adoption of QRIS innovation among MSMEs in Malang City who are members of ABM Preneur